Penerapan Sistem Akuntansi Syariah Berbasis Enterprise Resource Planning pada Lembaga Keuangan Mikro Syariah - Lubis, Ali Topan; Rukiah NST (Jurnal Akuntansi dan Pajak, 2026)
The research looks into how to create a clear plan for using the Sharia Accounting System (SAS) together with Enterprise Resource Planning (ERP) in Sharia Microfinance Institutions (LKMS) in Indonesia. The goal is to improve long-term performance and make sure the system follows Sharia principles. The study uses a detailed review of existing literature from Islamic accounting, computerized accounting systems, and how ERP systems are used in small businesses. The results show that ERP systems have a lot of potential to help with connecting different processes and providing up-to-date information, which is important for following Sharia rules. But for ERP to work well, it needs to fit well with the tasks it handles (Task Technology Fit) and have strong support from management. The ERP system should be built specifically to meet Sharia accounting standards, including how to report Zakat and Waqf, and should support the main goals of Sharia, like fairness and justice. This study provides a useful guide that connects the need for Sharia compliance with the complexity of ERP systems, helping LKMS and system developers focus on features that support Sharia audits, Zakat/Waqf reporting, and proper internal controls for better long-term performance.